Superior photoelectrochemical performance of Fe2O3/g-C3N4 heterostructure synthesized by chemical precipitation method. (2022) - Harak, Chetan; Mardikar, Satish; Gulavani, Vaibhavi; Yengantiwar, Ashish; Salve, Vaibhav; More, Paresh; Pandit, Vikram; Balgude, Sagar
Abstract: The Fe2 O3 /g-C3 N4 was fabricated via. chemical precipitation employing graphitic carbon nitride (GCN) and iron-nitrate precursors. XRD and FTIR spectroscopy were used to confirm phase identification and impurity study of the as-synthesized heterostructure. SEM was used to explore the morphology of the as-synthesized heterostructure. EDS confirmed the elemental composition of the Fe2 O3 /g-C3 N4 heterostructure. The UV–visible spectra were used to assess the optical properties, which revealed a band structure in the visible region that is favourable for photoelectrochemical performance. Using a simulated visible light source, the photoelectrochemical performance of the Fe2 O3 /g-C3 N4 heterostructure was examined, revealing a good photocurrent density of the as-synthesized heterostructure.